IMPROVING EFL LEARNERS SPEAKING PROFICIENCY THROUGH INSTAGRAM VLOG - Wulandari, Mega (LLT Journal: A Journal on Language and Language Teaching, 2019)
This research investigated whether Instagram Vlog contributed to the improvement of EFLs speaking ability. It also examined learners perceptions on the integration of Instagram Vlog in a speaking class. There were 28 participants involved in this research. To determine the impact of the Instagram Vlog on EFL learners speaking ability, pre- and post-tests were administered to measure the improvement. The results indicated that the implementation of Instagram Vlog into a basic-level speaking class improved the learners speaking proficiency in terms of pronunciation, fluency, vocabulary, syntax, and general use of the target language. The analysis of the questionnaire demonstrated that the utilization of Instagram vlog contributed to EFL learners speaking skill on enhancing fluency, acquiring vocabulary items, and boosting confidence and motivation.